The Effect of Flaxseed in Breast Cancer: A Literature Review - Calado, Ana; Neves, Pedro Miguel; Santos, Teresa; Ravasco, Paula (Frontiers in Nutrition, 2018)
Breast cancer is one of the most common cancers and the second most responsible for cancer mortality worldwide. In 2014, in Portugal, close to 27 200 people died of cancer, which 1791 were women with breast cancer. Flaxseed has been one of the most studied foods, regarding possible relations to breast cancer, though mainly in experimental studies in animals, yet in few clinical trials. It is rich in omega-3 fatty acids, alpha-linolenic acid, lignan and fibers. One of the main components of flaxseed are the lignans, of which 95% are made of the predominant secoisolariciresinol diglucoside (SDG). SDG is converted into enterolactone and enterodiol, both with anti-estrogen activity and structurally similar to estrogen; they can bind to cell receptors, decreasing cell growth. Some studies have shown that the intake of omega-3 fatty acids is related to the reduction of breast cancer risk. In animal studies, α-linolenic acid have been shown to be able to suppress growth, size and proliferation of cancer cells and also to promote breast cancer cell death. Other animal studies found that the intake of flaxseed combined with tamoxifen can reduce tumor size to a greater extent than taking tamoxifen alone. Additionally, some clinical trials showed that flaxseed can have an important role in decreasing breast cancer risk, mainly in postmenopausal women. Further studies are needed, specifically clinical trials that may demonstrate the potential benefits of flaxseed in breast cancer.